THE INFLUENCE OF HEALTH EDUCATION ABOUT REPRODUCTIVE HEALTH ON SEXUAL BEHAVIOR IN ADOLESCENTS AT SERUYAN CENTRAL STATE HIGH SCHOOL 2 SERUYAN DISTRICT - Devy Putri Nursanti; Eri Puji Kumalasari (Journal for Quality in Women's Health, 2025)
Sexual behavior during adolescence is a form of failure in sexual education that must be carried out during adolescence. Apart from that, negative sexual behavior carried out by teenagers will have an impact on the teenager's future life. One important effort to prevent teenagers from premarital sexual behavior is to educate teenagers about sexual behavior from an early age. The aim of this research is to analyze the effect of health education about reproductive health on sexual behavior in adolescents. In this research, researchers used a quantitative pre-experimental design with a one group pre test and post test design